Does corporate governance moderate the relationship between internal control system effectiveness and SMEs financial performance in Ghana? - Alhassan Musah; Abigail Padi; Bismark Okyere; Deodat E. Adenutsi; Charles Ayariga (Cogent Business & Management, 2022)
The study examined the effect of the major component of an internal control system according to the COSO framework on the financial performance of SMEs registered with the Association of Ghana Industries (AGI) in Ghana. The study further examined the moderating role of corporate governance practice on the relationship between the components of the internal control system and the financial performance of SMEs registered with AGI. The study surveyed 300 SMEs registered with AGI in Ghana using a questionnaire as the main instrument of data collection. The data were analysed using Pearson correlation analysis and hierarchical regression analysis to achieve the above-stated objectives. The results of the study showed that all the five major components of the internal control system (control environment, control activities, risk assessment, information, and communication and monitoring) have a positive and significant relationship with the financial performance of SMEs registered with AGI. The study further revealed that effective corporate governance practice moderates the relationship between all five components of the internal control system and the financial performance of SMEs registered with AGI in Ghana. The interaction between the independent variables and financial performance is stronger with the introduction of corporate governance practices.
Keywords: 650; corporate governance; financial performance; Ghana; Internal control systems; SMEs